AN E-LEARNING MODULE IN DRESSMAKING NATIONAL CERTIFICATE II - Bautista, Constantine M. (International Journal of Psychosocial Rehabilitation, 2020)
Abstract - This research study focused on the process and development of An E-learning Module for Dressmaking NC II with a teacher’s guide using the ADDIE model. A validated questionnaire was utilized in order for the respondents to evaluate the acceptability of the E-Learning Module in terms of its content validity and acceptability criteria.